Individualized Fortification Influences the Osmolality of Human Milk - Kreins, Nathalie; Buffin, Rachel; Michel-Molnar, Diane; Chambon, Veronique; Pradat, Pierre; Picaud, Jean-Charles (Frontiers in Pediatrics, 2018)
Background: Fortification of human milk (HM) increases its osmolality, which is associated with an increased risk of necrotizing enterocolitis. The impact of new fortifiers on osmolality is not well-known, nor are the kinetics regarding the increase in osmolality. Aim: To determine the optimum fortifier composition for HM fortification by measuring the osmolality of fortified HM made with three powder multicomponent fortifiers (MCFs) and a protein fortifier (PF). Methods: The osmolality of HM was assessed at 2 (H2) and 24 (H24) h after fortification to compare the effects of MCF (MCF1–3) and PF used in quantities that ensured that infants' nutrient needs would be met (MCF: 4 g/100 ml HM; PF: 0.5 g or 1 g/100 ml HM). To evaluate the early kinetics associated with the osmolality increase, the osmolality of HM fortified with MCF1 or MCF2 was also measured at 0, 1, 5, 10, 15, 20, 30, 40, 50, 60, 90, and 120 min after fortification. Results: The osmolality increased significantly immediately after fortification, depending on the type of fortification used and the quantity of MCF and PF used, rather than the time elapsed after fortification. The maximum value at H24 was 484 mOsm/kg. The mean increase in osmolality between H2 and H24 was 3.1% (p < 0.01) (range: 0.2–10.8%). Most of the increase (>70%) occurred immediately after fortification. Conclusion: When choosing a fortifier, its effect on HM osmolality should be considered. As most of the increase in osmolality occurred immediately, bedside fortification is not useful to prevent the increase in osmolality, and further research should focus on improving fortifier composition.